Parameter optimization for microwave coupled with hot air drying process of hawthorn slices using response-surface methodology - Yu, Haiming; Zuo, Chuncheng; Xie, Qiuju (International Journal of Agricultural and Biological Engineering, 2015)
The microwave coupled with hot air (MCHA) drying method was used in this test to dry hawthorn slices The effect of initial microwave power density level (6 W/g to 12 W/g), hot air temperature (55°C to 70°C), and hot air velocity (1 m/s to 3 m/s) on the quality attributes of rehydration ratio (Rf), organic acid (OA) and ascorbic acid (AA) of the dehydrated hawthorn slices was analyzed using a response surface methodology. An orthogonal rotatable central composite with three factors and at five levels was used to develop predictive regression models for the responses. The prediction mathematical model of Rf, OA and AA of the hawthorn slice was determined by analysis of variance. Factor and response variables as well as the prediction mathematical model, the optimal drying process of Rf, OA and AA of the hawthorn slice were determined by using the Design-Expert software. The comprehensive optimal conditions were as follows: initial microwave power density 12 W/g, hot air temperature 55°C and hot air velocity 1.56 m/s. Keywords: parameter optimization, response surface methodology, hot air drying, microwave, hawthorn slice DOI: 10.3965/j.ijabe.20150802.1596